Water-efficient technologies for vegetable production - Singh, D. K.; Bahadur, Anant; Prasad, R. N.; Singh, B. (Indian Horticulture, 2019)
The drip irrigation, regulated deficit irrigation, mulching, furrow irrigated raised bed planting, etc are the water efficient technologies that can be used in vegetable production for realization of higher water savings and enhancement in crop yield and quality.